Targeting autophagy using natural compounds for cancer prevention and therapy. Issue 8 (12th February 2019) - Deng, Shuo; Shanmugam, Muthu K.; Kumar, Alan Prem; Yap, Celestial T.; Sethi, Gautam; Bishayee, Anupam
Abstract : Autophagy, also known as macroautophagy, is a tightly regulated process involved in the stress responses, such as starvation. It is a vacuolar, lysosomal pathway for the degradation of damaged proteins and organelles in eukaryotic cells. Autophagy also plays a key role in various tissue processes and immune responses and in the regulation of inflammation. Over the past decade, three levels of autophagy regulation have been identified in mammalian cells: 1) signaling, 2) autophagosome formation, and 3) autophagosome maturation and lysosomal degradation. Any deregulation of the autophagy processes can lead to the development of diverse chronic diseases, such as diabetes, obesity, cardiovascular disease, neurodegenerative disease, and malignancies. However, the potential role of autophagy in cancer is rather complex and has been associated with both the induction and the inhibition of neoplasia. Several synthetic autophagy modulators have been identified as promising candidates for cancer therapy. In addition, diverse phytochemicals derived from natural sources, such as curcumin, ursolic acid, resveratrol, thymoquinone, and γ‐tocotrienol, also have attracted attention as promising autophagy modulators with minimal side effects. In this review, the authors discuss the importance of autophagy regulators and various natural compounds that induce and/or inhibit autophagy in the prevention and therapy of cancer. Abstract : Autophagy, an evolutionally conserved, tightly regulated process, can lead to the development of diverse chronic diseases, including cancer. Various bioactive natural compounds either induce and/or inhibit autophagy, with potential for cancer prevention and therapy.